The Implementation of the Deep Learning Approach in Al-Islam Learning at Muhammadiyah 06 Palembang Elementary School - Muhammad Farhan Ferdino; Kasinyo Harto; Febriyanti Febriyanti; Ermis Suryana; Baldi Anggara (FKIP - Universitas Riau, 2026)
The deep learning approach encourages learners to engage in meaningful, reflective, and enjoyable learning experiences to promote students’ deeper understanding. This study aimed to analyze the implementation of the deep learning approach through the principles of mindful, meaningful, and joyful learning in Al-Islam learning at SD Muhammadiyah 06 Palembang and to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative case study design. Observations, semi-structured interviews, and documentation were employed to obtain data from the principal, vice principal, and Al-Islam teacher in charge of curriculum affair. The data were examined through Miles and Huberman’s interactive analysis model, encompassing data reduction, data presentation, verification, and conclusion. The findings revealed that the deep learning approach was implemented through planning, implementation, and evaluation stages. Mindful learning fostered students’ critical and reflective thinking, meaningful learning connected learning materials with real-life experiences, and joyful learning created active and engaging classroom interactions. Supporting factors included school leadership, adequate facilities, teacher training, and a positive school culture. Meanwhile, limited teacher understanding, instructional time constraints, and diverse student abilities became inhibiting factors. The study concludes that the deep learning approach can enhance students’ understanding, critical thinking, and active participation in Al-Islam learning.